Assessment and Psychometric Properties of the 21-Item Depression Anxiety Stress Scale (DASS-21) among Portuguese Higher Education Students during the COVID-19 Pandemic - Carlos Laranjeira; Ana Querido; Pedro Sousa; Maria Anjos Dixe (MDPI AG, 2023)
The COVID-19 pandemic has caused substantial disruptions in the lives of higher education students, with detrimental repercussions for academic performance and overall mental health. Therefore, we aimed to evaluate the prevalence of depression, anxiety, and stress symptoms among Portuguese higher education students during the first wave of the coronavirus pandemic and investigate DASS-21's psychometric characteristics and whether it functions effectively during a pandemic. A convenience sampling procedure was used to recruit 1522 participants (75.1% women and 79.2% undergraduate students) for this cross-sectional research. Participants completed an e-survey created using DASS-21. The results revealed a considerable prevalence of symptoms of depression [≥10] (N = 434, 28.5%), anxiety [≥7] (N = 551, 36.2%), and stress [≥11] (N = 544, 35.7%). Confirmatory factor analysis (CFA) revealed the scale's three-factor structure, which matched the three DASS-21 subscales. Subsequently, the heterotrait-monotrait (HTMT) correlation ratio evaluated the scale's discriminant validity, which was relatively good. Cronbach's alpha measured the internal consistency of the DASS subscales, which was excellent (Cronbach's α > 0.90). DASS-21 was shown to be a reliable and appropriate measure for assessing students' mental health. Furthermore, DASS-21 is recommended for use by academics and healthcare professionals in measuring students' psychological distress. Further validation studies of this scale are needed with larger and more representative samples.